MAT 117 Week 6 Quiz Version 9 (Latest Version Got 100% Score A+ Guide)

MAT 117 Week 6 Quiz
MAT 117 Week 6 Quiz
MAT 117 Week 6 Quiz
MAT 117 Week 6 Quiz
MAT 117 Week 6 Quiz
The material presented below is not meant to be a comprehensive list of all you need to know in the content area. Rather it is a starting point for building your knowledge and skills. Additional study materials are recommended in each area below to help you master the material.
Your Answers: 9 / 9 Correct (100%)
1. If f(x) = sqrt(x^2-1) and g(x)=sqrt(x-1), which expression represents f(x)/g(x) for x1?
Sqrt(x)
Sqrt(x+1)
1/ Sqrt(x+1)
Sqrt(x-1)
2. Consider the diagram below.
The function h(x)=1/98 x^2 describes h(x), the height of part of a rollercoaster track, where x is the horizontal distance in feet from the center of this section of the track. The towers that support this part of the track are the same height and are 150 feet apart. Which is the best estimate of the height of the towers?
85.7 feet
57.4 feet
121.2 feet
229.6 feet
3. The profit P, in dollars, for a company is modeled by the function P(x) = -750x^2 + 15000x, where x is the number of items produced. For which values of x will the company lose money ?
x 20
2< x ≤ 10
10 < x < 20
x < 2
4. Nancy made the following statement:
The range of f(x) = ax + b is the set of all real numbers given that a and b are real numbers.
Which produces a counter example to her statement?
a = 0
a < 0
b = 0
b < 0
5. Consider the equations:
f(x) = -6x-1 and g(x) = 4x^2
Select the solution for (f+g)(x)
-6x-1+4x^2
-24x^3-4x^2
-24x^2-1
-6x-1-24x^2
6. Consider the equations:
f(x) = -6x-1 and g(x) = 4x^2
Select the solution for (fg)(x)
-6x-1+4x^2
-24x^3-4x^2
-24x^2-1
-24x^5
7. Select the x-coordinate of the vertex of the parabola defined by the function f(x) = -5×2 + 9x + 3.
8. Determine the equation of g(x) that results from translating the function f(x) = x^2 + 5 upward 9 units.
9. Determine the equation of g(x) that results from translating the function f(x) = (x + 10)^2 to the right 12 units.
g(x) = (x – 2)^2
g(x) = (x + 22)^2
g(x) = (x + 10)^2 – 12
g(x) = (x + 10)^2 + 12
Powered by